Country Economic Memorandum for Sao Tome and Principe - Background Note 3 : Where has Trade Growth Come from in São Tomé and Príncipe - Signoret, Jose E. (World Bank, Washington, DC, 2019)
This note examines the competitiveness of the export sector in São Tomé and Príncipe. It relies on the framework developed by Reis and Farole (2012) and examines the export competitiveness along four complementary dimensions: export growth and market shares, diversification in terms of product and destinations, quality of exports, and the survival or persistence of export flows. It uses export product level data for the period 2000-2017, as available, from international trade databases that help in benchmarking the performance of São Tomé and Príncipe with that of peer countries. Peer countries include, as data is available, Belize, Cabo Verde, Comoros, Dominica, Fiji, Mauritius, Maldives, Seychelles, St. Lucia and Vanuatu. While this note focuses on export outcomes, it also provides a brief picture on imports into São Tomé and Príncipe. The main findings of this note are as follows: Trade remains important for São Tomé and Príncipe, especially imports to satisfy local demand. Total exports have been increasing, both for goods and services. Goods exports, however, remain highly concentrated in cocoa exports to the EU market. Export trends for goods have tended to sustain this dependence, with very little expansion in the extensive margin, and thus with limited diversification of goods exports. This is despite relative comparative advantages in other agricultural products, such as coconuts, dried fruits, and seafood and preferential duty-free and quota-free access into the EU and other developed countries’ markets. Meanwhile, exports of services have increased rapidly, led by travel services. São Tomé and Príncipe exports more services than goods and it has become a net exporter of services. Creating strong (backward) linkages between the tourist industry and the rest of the economy could sustain growth in other industries that, in turn, can support export diversification.